2017
DOI: 10.1097/qai.0000000000001444
|View full text |Cite
|
Sign up to set email alerts
|

HIV and Obesity Comorbidity Increase Interleukin 6 but Not Soluble CD14 or D-Dimer

Abstract: Objectives Obesity prevalence among people living with HIV (HIV+) is rising. HIV and obesity are pro-inflammatory states, but their combined effect on inflammation (measured by interleukin 6, IL-6), altered coagulation (D-dimer), and monocyte activation (soluble CD14, sCD14) is unknown. We hypothesized inflammation increases when obesity and HIV infection co-occur. Methods The VACS survey cohort is a prospective, observational, longitudinal study of predominantly male, HIV+ veterans and veterans uninfected w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 67 publications
4
12
0
Order By: Relevance
“…In the present study, we found elevated concentrations of sCD14 in PLWH both with and without DM2 compared to both controls with DM2 and healthy controls. A larger study found decreased concentration of sCD14 in HIV/obese persons compared to HIV/non-obese persons [33]. In contrast, an increase in sCD14 concentration in overweight and obese PLWH gaining weight after initiation of cART has been reported [34].…”
Section: Discussionmentioning
confidence: 95%
“…In the present study, we found elevated concentrations of sCD14 in PLWH both with and without DM2 compared to both controls with DM2 and healthy controls. A larger study found decreased concentration of sCD14 in HIV/obese persons compared to HIV/non-obese persons [33]. In contrast, an increase in sCD14 concentration in overweight and obese PLWH gaining weight after initiation of cART has been reported [34].…”
Section: Discussionmentioning
confidence: 95%
“…In the present study, we found elevated concentrations of sCD14 in PLWH compared to uninfected controls, independently of DM2 status. A larger study found decreased concentration of sCD14 in HIV/obese persons compared to HIV/non-obese persons [33]. In contrast, an increase in sCD14 concentration in overweight and obese PLWH gaining weight after initiation of cART has been reported [34].…”
Section: Discussionmentioning
confidence: 95%
“…In the present study, we found elevated concentrations of sCD14 in PLWH both with and without DM2 compared to both controls with DM2 and healthy controls. A larger study found decreased concentration of sCD14 in HIV/obese persons compared to HIV/non-obese persons [ 38 ]. In contrast, an increase in sCD14 concentration in overweight and obese PLWH gaining weight after initiation of cART has been reported [ 39 ].…”
Section: Discussionmentioning
confidence: 99%